UKRAINIAN-JAPANESE RELATIONS IN THE 1950S – 1980S IN THE LIGHT OF SOURCES FROM THE DNIPRO COLLECTIONS (Південний архів (історичні науки), 2022)
The purpose of the article is to reveal the content of Ukrainian-Japanese relations in the 1950s – 1980s on the basis of regional sources, namely, archival and library collections of Dnipro. The problem that led to the appeal to the topic is the lack of knowledge of both the place of Ukraine in the international relations of the USSR during the Cold War, and the data resource that allows you to explore this place. The methodology of the study is based on a systematic approach, which provided for the “placement” of Ukrainian-Japanese relations in the context of Soviet-Japanese relations in the 1950s – 1980s, and a regional one, which led to a focus on the source complexes of the Dnipro. Descriptive, historical-chronological, comparative methods are used. Results. The state of the topic study in Ukrainian and foreign historiography is considered and it is established that the period of the 1950s – 1980s in the history of Ukrainian-Japanese relations is at the margin of interests of scientists. The redirection of attention from the Moscow center as the leader of the general foreign policy strategy to the republican dimension, in this case the Ukrainian one, made it possible to raise the question of the role of different actors in the international relations of the USSR. The information potential of several funds of the State Archives of the Dnipropetrovsk region was found out: the Ministry of Ferrous Metallurgy of Ukraine, the Institute of Ferrous Metallurgy of Ukraine, the Dnіpropetrovsk/Pridneprovsk economic region, which accumulate a significant part of the materials on the history of economic cooperation between the USSR and the “capitalist” countries, to which Japan belonged. The enterprises of Ukraine, which took the lead in economic contacts with Japan, were identified – the Nikopol South Pipe Plant and the mining complex of Kryvyi Rih, as well as the main Japanese partners who showed interest in cooperation. Most of these enterprises are still leaders in Japan’s heavy industry. The materials of the regional press, factory newspapers supplemented and enriched the idea of the content of relations, revealed the specifics of its presentation through the prism of the Cold War events. Conclusions. Thanks to a significant resource of heavy industry, in particular ferrous metallurgy, Ukraine occupied an important place in Soviet-Japanese relations. The peculiarity of these relations was their limitedness at the regional level, “point” due to purely economic needs, closeness to the broad masses, in contrast to ties with “friendly” countries from the socialist camp or with governments loyal to the USSR from Third World countries. The sources reveal not only the production content of relations, but also its sociocultural profile: the practice of receiving Japanese delegations, its composition and level of representation, specifics of relations with Japan along with other countries who had a market economy.
Keywords: Ukraine, Japan, USSR, politics, economic relations, Dnіpropetrovsk, Dniprovsky region.